Implementasi Kebijakan Kesejahteraan Sosial Lanjut Usia: Telaah Isi dan Lingkungan Kebijakan (Model Grindle) (Studi UPTD Kesejahteraan Sosial Lanjut Usia di Kupang) - Amalya Lewa, Irvan; Putu Yoga Bumi Pradana, I; Nursalam, Nursalam (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This study aims to analyze the implementation of social welfare policy for older persons carried out by the Regional Technical Implementation Unit (UPTD) for Elderly Social Welfare in Kupang and to identify the factors that hinder its implementation. The study applies Grindle’s policy implementation framework, which emphasizes two key dimensions: policy content and policy context. A qualitative research approach was employed, with data collected through observation, in-depth interviews, and documentation. The data were obtained from nine purposively selected informants and relevant policy-related documents. The findings indicate that the implementation of the elderly social welfare policy has been carried out but has not yet been optimal. Based on Grindle’s analytical model, several issues were identified, including the relevance of service programs, the recruitment process of implementers, budget allocation and efficiency, and the capacity of human resources. These findings imply the need for policy evaluation and the strengthening of implementation governance through needs-based program adjustments, improved resource management, and capacity building of implementers to ensure that policy objectives are achieved more effectively and sustainably.